Late presentation of Ellis van Creveld Syndrome with Common atrium anomaly: A case report in a Nepalese Adult - Hirachan, Anish; Bishal, KC; Maskey, Arun; Roka, Madhu; Hirachan, Gopi Prasad (Journal of Advances in Internal Medicine, 2018)
Ellis Van Creveld syndrome (EVC) is a rare genetic disorder having autosomal recessive inheritance characterized by chondrodystrophy, polydactyly, ectodermal dysplasia, and various cardiac anomalies. Acromelic shortening of upper and lower limbs, genu valgum, deformed teeth, short ribs and narrow thorax and other systemic anomalies complete the picture of this syndrome. The patients with the syndrome rarely survive into adulthood. Here, we report a 30 year old male with EVC presenting for the first time in middle age with Common atrium anomaly.